Pertumbuhan dan Hasil Genotipe Bawang Merah pada Peningkatan Dosis Sulfur melalui Sistem Hidroponik Nutrient Film Technique - Noor Farid; Zulfa Ulinnuha (Universitas Pekalongan, 2022)
Shallots are one of the commodities with high economic value. This study aims to determine (1) the effect of each dose and genotype of sulfur on the growth and yield of shallots, (2) to determine the interaction of sulfur and genotype on the growth and yield of the tested genotypes and comparison varieties. This research was carried out from August to November 2019 at the screenhouse of the Faculty of Agriculture, Jenderal Soedirman University, Grendeng Village, North Purwokerto District, Banyumas Regency at an altitude of 110 m above sea level. The experimental design used was the RAKL (Completely Randomized Design) with 3 replications. The first factor to be tested was the dose of sulfur (S) which consisted of S1 (30 ppm) and S2 (90 ppm) and the second factor was the genotype (G) which consisted of fifteen genotypes and five comparison varieties. The characteristics observed in this study were: plant height, number of leaves, leaf length, leaf diameter, root weight, plant wet weight, plant dry weight, number of tubers, tuber diameter, tuber wet weight, tuber dry weight. The results showed that (1) increasing the dose of sulfur increased the number of leaves, leaf length, root length, plant dry weight and tuber dry weight, (2) The interaction between genotype and sulfur was found in characters such as leaf length, leaf diameter, root volume, root length. root, plant dry weight, tuber diameter, tuber wet weight and tuber dry weight, (4) Bima Juna varieties, genotypes G3, G11, G15, G16, G17, G22, G23, G24, G79, C4 experienced an increase in tuber dry weight at dose of 90 ppm.